Pengaruh Model Pembelajaran Flipped Classroom Dengan Menggunakan Media Interaktif Video Terhadap Hasil Belajar Siswa Kelas X IIPS Pada Mata Pelajaran Ekonomi - Qurratul Aini; Susilawati Susilawati (Universitas Hamzanwadi, 2022)
The type of research used is experimental research. The population in this study were all students of class X IPS. Which consists of class X IPS A, X IPS B, X IPS C. While the sample used is class X IPS A as the experimental class and class X IPS B as the control class. To test the data prerequisites, the data normality test was carried out with the Kolmogorov - Smirnov test and the homogeneity test of the data was carried out by the Levene statistic test, while the hypothesis test used the paremetric statistical test. In the experimental class, the highest score was 95 and the lowest score was 76 with a post-test average of 82.03 and a standard deviation of 5.245. Meanwhile, in the control class, the highest score was 90 and the lowest score was 60 with an average post-test score of 76.13 and a standard deviation of 7.074. For the results of hypothesis testing for learning outcomes for the experimental class and control class, the significance value (2-tailend) on the t-test for Equality of Means is 0.000 < 0.05, meaning Ho is rejected and Ha is accepted. This means that the use of the Flipped Classroom Learning Model by Using Video Interactive Media has a Positive and Significant Effect on the Learning Outcomes of Class X Social Studies Students in Economics Subjects at SMAN 1 Suela